2009
DOI: 10.1007/s11293-009-9199-1
|View full text |Cite
|
Sign up to set email alerts
|

Convergence in Revealed Preferences for Automobiles as Differentiated Goods: U.S. and OECD Countries: 1970–1999

Abstract: Convergence, Differentiated goods, Revealed preferences, Globalization, E21, F15,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A similar observation has been made in several prior studies with a more global focus (e.g.,Sebri and Zaccour 2017, p. 125; Talukdar et al 2002, p. 102).4 Initially, b-convergence was used primarily in the macro-economics field (see, for example, Islam 2003 for a review). More recently, the application domain has expanded considerably with, among others, studies on the convergence of car prices(Goldberg and Verboven 2005), retail gasoline prices(Suvankulov et al 2012), retail payment methods(Martikainen et al 2015), or consumers' revealed preferences for car attributes(Silver 2010).K. Gielens, M.G.…”
mentioning
confidence: 99%
“…A similar observation has been made in several prior studies with a more global focus (e.g.,Sebri and Zaccour 2017, p. 125; Talukdar et al 2002, p. 102).4 Initially, b-convergence was used primarily in the macro-economics field (see, for example, Islam 2003 for a review). More recently, the application domain has expanded considerably with, among others, studies on the convergence of car prices(Goldberg and Verboven 2005), retail gasoline prices(Suvankulov et al 2012), retail payment methods(Martikainen et al 2015), or consumers' revealed preferences for car attributes(Silver 2010).K. Gielens, M.G.…”
mentioning
confidence: 99%